2016
DOI: 10.1002/jnm.2203
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design of wideband digital integrators and differentiators using harmony search algorithm

Abstract: This paper presents an efficient approach to design stable, wideband, and infinite impulse response digital integrators (DIs) and digital differentiators (DDs) of first, second, third, and fourth order using an evolutionary optimization algorithm called harmony search (HS). In recent years, although wideband DIs and DDs have been designed using metaheuristic optimization techniques such as simulated annealing, genetic algorithm, and particle swarm optimization (PSO), these algorithms lead to sub‐optimal soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 54 publications
(94 reference statements)
0
28
0
Order By: Relevance
“…From Table , it can be observed that RMSME value of −23.42 dB is obtained by Mahata et al, whereas, the proposed approach results in the lowest RMSME value of −24.95 dB. This ensures an improvement of 6.53% in the proposed SSA‐based DD over the DD reported in Mahata et al The percentage of improvement (PI) incurred by the proposed approach over all the reported state‐of‐the‐art DDs by considering the RMSME metrics is presented in Table .…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…From Table , it can be observed that RMSME value of −23.42 dB is obtained by Mahata et al, whereas, the proposed approach results in the lowest RMSME value of −24.95 dB. This ensures an improvement of 6.53% in the proposed SSA‐based DD over the DD reported in Mahata et al The percentage of improvement (PI) incurred by the proposed approach over all the reported state‐of‐the‐art DDs by considering the RMSME metrics is presented in Table .…”
Section: Resultsmentioning
confidence: 84%
“…The FIR filter‐based designs are inherently stable and provide linear phase characteristics . However, to meet the same magnitude response characteristic, the FIR filter‐based approach needs higher filter order than IIR‐based approach . Several numerical methods‐based digital integrators (DIs) and DDs are reported in the literature .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature survey reveals that metaheuristics have shown promising results in the field of digital filter design [16,17,18]. Hence, more research effort should be directed towards the design of NOIs based on the nature-inspired optimization algorithms.…”
Section: Introductionmentioning
confidence: 99%